Populærmusikk fra Korgen - Larsen, Ove (Tidsskrift for kulturforskning, 2015)
The article leans on a narrative form in its presentation of five boys in a rural landscape. Located in Korgen, a small community in Northern Norway, and set in the late -60's, it tells the story of the reception and involvement with the Anglo-American popular music of the times. The article is partly autobiographical as the author is one of the actors in this story. Through humorous and sincere snapshots the article tries to give an insight into the lives of rural teenagers. The article gives an account of how a seemingly urban youth culture found its way into a remote Norwegian community. It addresses issues such as gaining access to instruments and equipment, learning how to play, and adopting the right looks. This process is described as an expansion and reinvention of the existing tradi-tions and norms, and as such the introduction of youth-revolt in Korgen was more of an evolution than a revolution.